Salt‐Stabilized Silylzinc Pivalates for Nickel‐Catalyzed Carbosilylation of Alkenes. (28th February 2022) - Wang, Jixin; Duan, Zhili; Liu, Xingchen; Dong, Shoucheng; Chen, Kaixin; Li, Jie
Abstract: We herein report the preparation of solid and salt‐stabilized silylzinc pivalates from the corresponding silyllithium reagents via transmetalation with Zn(OPiv)2 . These resulting organosilylzinc pivalates show enhanced air and moisture stability and unique reactivity in the silylative difunctionalization of alkenes. Thus, a practical chelation‐assisted nickel‐catalyzed regioselective alkyl and benzylsilylation of alkenes has been developed, which provides an easy method to access alkyl silanes with broad substrate scope and wide functional group compatibility. Kinetic experiments highlight that the OPiv‐coordination is crucial to improve the reactivity of silylzinc pivalates. Furthermore, late‐stage functionalizations of druglike molecules and versatile modifications of the products illustrate the synthetical utility of this protocol. Abstract : A new type of salt‐stabilized solid silylzinc pivalate prepared from the silyllithium reagents via transmetalation with Zn(OPiv)2 is reported. These silylzinc pivalates showed enhanced air and moisture stability and unique reactivity in the nickel‐catalyzed regioselective alkyl and benzylsilylation of alkenes. Kinetic experiments highlighted the crucial involvement of OPiv‐coordination in improving the reactivity of silylzinc pivalates.